Respostas
respondido por:
7
4x² + 4x + 1 = 0
a = 4
b = 4
c = 1
Δ = b² - 4ac
Δ = 4² - 4 * 4 * 1
Δ = 16 - 16
Δ = 0
x = - b ± √Δ
2a
x = - 4 ± √0
2 * 4
x' = - 4 - 0 = - 4 = - 2 = - 1
8 8 4 2
x'' = - 4 + 0 = - 4 = - 2 = - 1
8 8 4 2
Como o delta (Δ) é igual a zero, as raízes da equação serão iguais, neste caso -1/2.
Espero ter ajudado. Valeu!
a = 4
b = 4
c = 1
Δ = b² - 4ac
Δ = 4² - 4 * 4 * 1
Δ = 16 - 16
Δ = 0
x = - b ± √Δ
2a
x = - 4 ± √0
2 * 4
x' = - 4 - 0 = - 4 = - 2 = - 1
8 8 4 2
x'' = - 4 + 0 = - 4 = - 2 = - 1
8 8 4 2
Como o delta (Δ) é igual a zero, as raízes da equação serão iguais, neste caso -1/2.
Espero ter ajudado. Valeu!
respondido por:
0
4x² + 4x + 1 = 0a = 4b = 4c = 1 Δ = b² - 4ac Δ = 4² - 4 * 4 * 1 Δ = 16 - 16 Δ = 0 x = - b ± √Δ 2a x = - 4 ± √0 2 * 4 x' = - 4 - 0 = - 4 = - 2 = - 1 8 8 4 2 x'' = - 4 + 0 = - 4 = - 2 = - 1 8 8 4 2
Como o delta (Δ) é igual a zero, as raízes da equação serão iguais, neste caso -1/2.
Como o delta (Δ) é igual a zero, as raízes da equação serão iguais, neste caso -1/2.
Perguntas similares
7 anos atrás
7 anos atrás
7 anos atrás
10 anos atrás
10 anos atrás
10 anos atrás
10 anos atrás